Sequencing the Plastid Genome of Giant Ragweed (Ambrosia trifida, Asteraceae) From a Herbarium Specimen - Sablok, Gaurav; Amiryousefi, Ali; He, Xiaolan; Hyvönen, Jaakko; Poczai, Péter (Frontiers in Plant Science, 2019)
We report the first plastome sequence of giant ragweed (Ambrosia trifida); with this new genome information, we assessed phylogeny of Asteraceae and the transcriptional profiling against glyphosate resistance in giant ragweed. Assembly and genic features show a normal angiosperm quadripartite plastome structure with no signatures of deviation in gene directionality. Comparative analysis revealed large inversions across the plastome of giant ragweed and the previously sequenced members of the plant family. Asteraceae plastid genomes contain two inversions of 22.8-kb and 3.3-kb, with the former located between trnS-GCU and trnG-UCC genes, while the other is between trnE-UUC and trnT-GGU genes. The plastid genome sequences of A. trifida and the related species, A. artemisiifolia, are identical in gene content and arrangement, but they differ in length. The phylogeny obtained is well resolved and congruent with previous hypotheses about phylogenetic relationship of Asteraceae. The origin of Ambrosia is dated to ca. 16 My BP (13 - 20 My BP). Expression divergence revealed differences in the relative expressions at the exonic and intronic levels providing hints towards the ecological adaptation of the genus. Giant ragweed shows various levels of glyphosate resistance with introns displaying higher expression patterns in resistant time points after the assumed herbicide treatment.